Bitter Kola (Garcinia kola) as Herbal Remedy for Diabetes - Nkereuwem S. Etukudoh; Obeta M. Uchejeso; Ibanga I. Etim (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Bitter Kola (Garcinia kola) is highly valued in Herbal / African folk medicine because of its varied and numerous uses which are social, economic and medicinal, thus making it an essential ingredient in African medicine. The study reviews some related literature on the action of bitter kola on diabetes. Medicinal plants such as Bitter kola are believed to be an important source of kolavirons and flavonoids as phytochemical components with potential therapeutic benefits for diabetes and other ailments. Bitter kola has antiinflammatory, analgesic, molluscidal, anti-atherogenic, antioxidant and hepatoprotective properties and should not be totally ignored in medical conditions including diabetes. From our published work, the serum glucose concentration of treated diabetic rats was significantly reduced (P > 0.05) compared to the serum glucose concentration of untreated diabetic rats and that of the controls. The reduced serum glucose concentration and that of concentrations of the lipid profile parameters attributed to the anti-diabetic and anti-hyperlipidemic activities of the bitter kola seed extract. The reduced glucose concentration could be due to the activity of bitter kola seed extract against inflammation and reactive oxygen species (ROS) of free radical on the pancreatic beta cells. This chapter shall be useful to researchers interested in authenticating the hidden truth which has not been scientifically validated about bitter kola especially with regards to diabetes.